The Crack Lung – A Case Report - Lopes, Débora; Gorgulho, Cátia; Ribeiro, Joana; Real, André Neto; Catorze, Nuno (Brazilian Journal of Case Reports, 2024)
Cocaine is an alkaloid extracted from the leaves of Erythroxylon coca and was first isolated in 1859. Cocaine induces both acute and chronic toxicity, affecting virtually every organ system. A 32-year-old male patient, with a history of post-traumatic epilepsy and substance abuse involving cannabinoids and cocaine, presented to the Emergency Department (ED) following self-limited seizures. Arterial blood gas analysis revealed hypoxemic respiratory failure, while blood tests showed no significant abnormalities. A thoracic computed tomography (CT) scan demonstrated extensive consolidations in most of the lower, middle, and upper pulmonary lobes. Transthoracic ultrasound suggested signs of non-compacted cardiomyopathy, and pulmonary ultrasound revealed a B-line pattern bilaterally. The patient was admitted to the Intensive Care Unit (ICU), due to respiratory insufficiency requiring invasive ventilation. Over time, his respiratory failure progressively improved, allowing extubation on the eighth day of hospitalization. He was discharged after two weeks and referred for follow-up consultations in Neurology, Psychiatry, and Cardiology. A follow-up CT scan performed three weeks after discharge showed resolution of the pulmonary consolidations and ground-glass opacities. Furthermore, a cardiac magnetic resonance imaging (MRI) study conducted five weeks post-discharge ruled out non-compacted cardiomyopathy. Cocaine-induced lung alterations are diverse and often nonspecific, making their diagnosis reliant on thorough clinical and radiological correlation. In this case, pulmonary parenchymal changes observed on the CT scan and severe respiratory failure raised suspicion for crack lung. Other potential diagnoses, such as cardiogenic and neurogenic pulmonary edema, were excluded.